I am having trouble differentiating without using the chain rule and I am looking for a quick explanation. Differentiate y=3sinx - 4cosx

you shouldn't be using chain rule in this case.Chain rule should be used when one variable is into another, had it been like,y= 3 sin ( cos 4x)in this case you use chain rule.for the given, equation,y= 3 sin x - 4 cos xdy/dx = 3 d/dx ( sin x) - 4 d/dx ( cos x) = 3 cos x - 4(-sin x) = 3cos x + 4 sinxPlease appreciate my help, by selecting my answer as the best, and add me as your tutor, Thanks!

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up